2009
DOI: 10.1074/jbc.m109.023135
|View full text |Cite
|
Sign up to set email alerts
|

α-Helical Domains Promote Translocation of Intrinsically Disordered Polypeptides into the Endoplasmic Reticulum

Abstract: Co-translational import into the endoplasmic reticulum (ER) is primarily controlled by N-terminal signal sequences that mediate targeting of the ribosome-nascent chain complex to the Sec61/translocon and initiate the translocation process. Here we show that after targeting to the translocon the secondary structure of the nascent polypeptide chain can significantly modulate translocation efficiency. ER-targeted polypeptides dominated by unstructured domains failed to efficiently translocate into the ER lumen an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
50
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(54 citation statements)
references
References 54 publications
4
50
0
Order By: Relevance
“…Yellow, small ribosomal subunit; gray, large ribosomal subunit; green, tRNA; blue, translocon. The model is based on the experiments described in this study and previous work (19,57).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Yellow, small ribosomal subunit; gray, large ribosomal subunit; green, tRNA; blue, translocon. The model is based on the experiments described in this study and previous work (19,57).…”
Section: Discussionmentioning
confidence: 99%
“…Secretome-Previous studies on the biogenesis of pathogenic mutants of the prion protein and model substrates revealed that IDPs equipped with an N-terminal signal peptide are inefficiently imported into the ER (18,19,44). Based on these findings, we performed an in silico screen for the identification of secretory proteins that are dominated by intrinsically disordered domains (Ͼ70% of the amino acid sequence).…”
Section: Intrinsically Disordered Proteins Are Underrepresented In Thementioning
confidence: 99%
See 3 more Smart Citations